2012
DOI: 10.1016/j.eplepsyres.2011.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic mossy fiber sprouting is related to the degree of cortical damage in three mouse strains

Abstract: Summary Controlled cortical impact injury was used to examine relationships between focal posttraumatic cortical damage and mossy fiber sprouting (MFS) in the dentate gyrus in three mouse strains. Posttraumatic MFS was more robust when cortical injury impinged upon the hippocampus, versus contusions restricted to neocortex, and was qualitatively similar among CD-1, C57BL/6, and FVB/N background strains. Impact parameters influencing injury severity may be critical in reproducing epilepsy-related changes in neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 19 publications
1
39
0
Order By: Relevance
“…Our results support previously published observations that demonstrated robust mossy fiber sprouting in the IML of the hippocampus following FPI and/or CCI (Golarai et al, 2001;Santhakumar et al, 2001;Hunt et al, 2009Hunt et al, , 2010. Several important factors might affect mossy fiber sprouting and seizure incidence after brain injury, such as impact parameters, injury location, animal age, and rodent species (Hunt et al, 2012). In addition, excitatory drive to surviving hilar GABAergic interneurons after CCI may be enhanced by convergent input from both pyramidal and granule cells resulting in network destabilization (Hunt et al, 2011).…”
Section: Brain Pathologysupporting
confidence: 88%
“…Our results support previously published observations that demonstrated robust mossy fiber sprouting in the IML of the hippocampus following FPI and/or CCI (Golarai et al, 2001;Santhakumar et al, 2001;Hunt et al, 2009Hunt et al, , 2010. Several important factors might affect mossy fiber sprouting and seizure incidence after brain injury, such as impact parameters, injury location, animal age, and rodent species (Hunt et al, 2012). In addition, excitatory drive to surviving hilar GABAergic interneurons after CCI may be enhanced by convergent input from both pyramidal and granule cells resulting in network destabilization (Hunt et al, 2011).…”
Section: Brain Pathologysupporting
confidence: 88%
“…A diffusion tensor imaging study conducted on a FPI rat model at 6 -12 mo postinjury showed that injured animals had thicker mossy fibers, decreased myelinated axons within the CA3 region and increased mossy fiber sprouting within the dentate gyrus (42). However, these processes abort without becoming functional (43)(44)(45). Since a role of PLs in axonal growth and sprouting is suggested by studies showing synthesis of PC, PE, and SM within axons (46,47), PL changes after injury in the hippocampi may be associated with self-reparative processes.…”
Section: Discussionmentioning
confidence: 99%
“…A variable degree of mossy fiber sprouting and synaptic reorganization in the dentate gyrus, as well as axon sprouting onto hilar interneurons has also been observed in concert with development of PTE and other forms of acquired epilepsy (19,22,26,29,35,36). Mossy fiber sprouting is localized to areas near the injury epicenter after focal injury (29) and is less severe and sparser after TBI than, for example, in chemoconvulsant models of TLE, but its presence, however limited, is a consistent feature of both models. Other cellular outcomes identified in both TLE and PTE models include an increase in postinjury granule cell progenitor proliferation and a reorganization of GABA A receptors in granule cells (33,(37)(38)(39)(40).…”
Section: Convergence Of Cellular Changes In Pte and Tle Modelsmentioning
confidence: 99%
“…The injury occasionally results in early seizures (<24 hours) (22,25), and spontaneous convulsive seizures develop in 40 to 50% of mice within approximately 8 weeks after severe injury (22,23,(26)(27)(28)) and 9 to 20% of mice after more moderate injuries (18,22,26). Like other murine epilepsy models, mouse strain may also influence seizure phenotype and the incidence of PTE (18,29). Seizures after CCI are similar to spontaneous behavioral and electrographic seizures that have been described in rats after LFPI (19) and in models of acquired TLE (30,31).…”
Section: Rodent Modelsmentioning
confidence: 99%